Time, leisure and well-being - Zuzanek, Jiri; Blackshaw, Tony (New York Routledge, 2021)
This publication looks at the relationship between leisure, labour, and well-being, first, through lens, by examining conflicting views of the leading minds of the past, and, second, by looking at what the 'unit-ideas' approach tells us about the relationship between work and leisure today, based on the analyses of current survey data, collected in part by the author
1. Leisure that never existed before: a historical perspective -- 2. Was Plato a friend or a foe of leisure? -- 3. Aristotle: philosopher of leisure and happiness -- 4. Leisure in Ancient Rome: otium and panem et circenses -- 5. Seneca: philosopher of tranquility and sadness -- 6. From the vale of tears to the Renaissance -- 7. St. Augustine: leisure and well-being in the Earthy City and the City of God -- 8. Thomas Aquinas: vita activa or vita contemplativa? -- 9. Work and leisure in Thomas More's Utopia -- 10. Montaige's essays and Pacal's Pensees: of diversion and happiness -- 11. Enlightenment's vision of work, leisure , and the arts -- 12. Adam Smith: capitalism with a human face? -- 13. The 19th century...was there ever a golden age? -- 14. Alexis de Tocqueville: why are Americans restless amidst prosperity? -- 15. Karl Marx: between the 'realm of freedom' and 'material necessity' -- 16. Emile Durkheim: of labor , leisure, and anomie -- 17. Max Weber: of work ethic, leisure, and disenchantment -- 18. Thorstein Veblen: from the ethics of work to conspicuous consumption -- 19. The 20th century: farewell to the 'Belle Epoque' -- 20. John Huizinga: sub specie ludi -- 21. Pitirim Sorokin: at the crossroad of ideational and sensate cultures -- 22. Josef Pieper: apology for Vita Contemplativa -- 23. Hannah Arendt: of 'human condition' -- 24. From the middletown and middletown in transition to the lonely crowd -- 25. Leisure research yesterday and today: Quo Vadis? -- 26. What happened to the society of leisure -- 27. Work-leisure relationship: the 'long arm of work'? -- 28. Leisure and social prestige: keeping up with the Joneses? -- 29. The pros and cons of the 'democratization of culture' -- 30. Of happiness, leisure, and riches
Includes bibliographical references and index
Keywords: Time management -- Cross-cultural studies; Leisure -- Cross-cultural studies; Well-being -- Cross-cultural studies